Domestic wastewater treatment system using waste plastic bottle caps as biofilter media - Muliyadi, Muliyadi; Purwanto, Purwanto; Sumiyati, Sri; Budiyono, Budiyono; Utomo, Sudarno; Warsito, Budi (Institute of Advanced Engineering and Science, 2025)
The increasing lack of clean water has created a paradigm for treating wastewater directly from the source. This study aimed to determine the effectiveness of processing domestic waste using plastic bottle caps in the anaerobe and aerobe reactor system by measuring several key parameters in wastewater. Experimental study on on-site wastewater treatment system using two bioreactors, a biodegradation made from fruit and vegetable peel waste, and local microorganisms. Domestic wastewater was used in this study. The wastewater treatment system's performance was monitored using parameters like pH, temperature, total suspended solids (TSS), chemical oxygen demand (COD), and biochemical oxygen demand (BOD), collected daily at 9 am during peak wastewater generation. The wastewater treatment system using aerobe and anaerobic reactors with plastic bottle cap media and microorganism biodegradation effectively reduced the TSS, COD, and BOD. The anaerobe reactors were more effective at removing these pollutants, with a maximum TSS reduction of 81.1%, COD removal efficiency of 90.1%, and BOD removal efficiency of 80.2%. The longer acclimatization time of the anaerobe reactor may make it more efficient after acclimatization compared to the aerobe reactor. Although the anaerobe reactor may require a longer acclimatization time, it ultimately results in a higher efficiency in terms of TSS, COD, and BOD reduction compared to the aerobe reactor.